GOUT ARTHRITIS DISTAL DIBULA MIMICKING BONE TUMOR: A CASE REPORT - Mujaddid Idulhaq; Arie K; Leli Sabariyah; Yuni Prasetyo Kurniati (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Gout is a picturesque presentation of uric acid disturbance. The clinical picture of gout is divided into asymptomatic hyperuricemia, acute gouty arthritis, intercritical period, and chronic tophaceous gout. The tophus found on gouty arthritis has clinical resemblance to neoplastic lesions such as epidermoid cysts therefore it is often mistaken. Diagnosis of gout is based on the history, the laboratory result, ultrasonography and histopathological examination. Management of gout includes management of flares, chronic gout, as well as management of comorbidities. Keywords: Gout arthritis, distal fibula, tophus, bone tumour